ENHANCED OCCUPANCY DETECTION SYSTEM USING ULTRASONIC/PIR SENSORS: IMPROVING ACCURACY AND EFFICIENCY IN SMART ENVIRONMENTS - Sougandhika Tera; Sai Praneeth Reddy Kolan (Proceedings on Engineering Sciences)
This innovative enhanced occupancy detection system provides a comprehensive solution to address the limitations of existing occupancy sensors in a wide range of applications. The incorporation of two ultrasonic/PIR sensors within the system ensures enhanced accuracy and reliability in detecting human presence and movement. By leveraging the unique strengths of both sensor types, the system overcomes the challenges faced by single-sensor systems, resulting in improved detection performance. The sequential activation of sensors allows for precise control of electrical appliances, effectively reducing false triggers and optimizing energy consumption. Another notable advantage of this system is its ability to operate optimally even in scenarios where obstacles obstruct the line of sight, thanks to its wider detection range. Through rigorous testing and thorough analysis, the system has proven to deliver high levels of accuracy, sensitivity, and reliability. With its potential to optimize energy efficiency, generate cost savings, and enhance user convenience, this advanced occupancy detection system holds great promise for revolutionizing a variety of settings such as smart homes, offices, healthcare facilities, and retail stores.